Foreign bodies inside us - Trends and knowledge regarding long-acting reversible contraceptives (LARCs) use, factors influencing of contraceptives choice-making process, and the dual-method use among Polish college-aged women - Aleksandra Nowak; Alicja Nowak; Magdalena Kiełbowicz (Kazimierz Wielki University, 2023)
Introduction: The choice-making process of the contraceptive method seems complex and influenced by many factors. Long-acting reversible contraceptives require mechanical interference with the woman's body. For some, it will be an insurmountable barrier whilst for others a chance to enjoy a successful sex life without fear of pregnancy. Recognizing the factors influencing their use will allow us to identify target groups, increase awareness, and spread knowledge about them. Purpose: This study aimed to assess contraceptive use trends and knowledge, focusing on long-acting reversible contraceptives (LARCs) and vaginal rings, also to identify predictors associated with their use and analyze the decision-making process for dual-method use (hormonal plus barrier method) among female college students in Poland. Materials and methods: A self-administered questionnaire including 44 questions in the form of a web-based survey distributed among peers in social media platforms and forums. Results: In the survey a total of 700 female students aged 19±25 took part. All the questions about LARC and vaginal rings were answered correctly by only 19 participants (2.71%). The most knowledgeable were medical students (p<0.0001). Out of 55 LARC and vaginal ring users (7.86%), 47 female students (76.4%,) stated the improvement of their life. Of the methods interfering with the body, the study group most frequently chose the vaginal ring (38.1%) and least frequently the hormone injection (0.1%).  Conclusions: Participants' knowledge of LARC methods and vaginal rings is insufficient and its main influencing factors are faculty type and frequency of intercourse. LARC and vaginal disc are not the first contraception choice. Fear of pregnancy is the most common factor for dual method use.